Environmental, Social, and Governance (ESG) Disclosure and Firm Size as Firm Value Estimators: The Role of Investment Return - Tiranda, Yan Paresae; Sembiring, Ferikawita Magdalena; Simatupang, Frido Saritua (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to examine and provide evidence on how Environmental, Social, and Governance (ESG) disclosure and firm size affect firm value, as well as the role of profitability from investment activities in moderating these relationships. The sample consists of companies included in the IDX ESG Leaders index, which also have ESG scores, requiring them to implement ESG practices—including green investments—as part of their commitment to sustainability. Data were analyzed using panel data regression and Moderated Regression Analysis (MRA). The findings reveal that ESG disclosure has a positive impact on firm value, whereas firm size has a negative impact on firm value. These results suggest that sustainability disclosure can foster innovation, enhance corporate reputation, and ultimately create long-term firm value. However, larger firms, despite their ability to adopt sustainability principles, may not consistently achieve optimal efficiency in performance monitoring, which may reduce firm value. Furthermore, the profitability or return on investment (ROI) in green investments was found not to moderate the effect of either ESG disclosure or firm size on firm value. These findings contribute to the sustainability literature, suggesting that firms need to integrate ESG strategies and green investments more effectively to enhance long-term firm value.